2005
DOI: 10.1073/pnas.0500848102
|View full text |Cite
|
Sign up to set email alerts
|

HIV binding, penetration, and primary infection in human cervicovaginal tissue

Abstract: We have developed human cervicovaginal organ culture systems to examine the initiating events in HIV transmission after exposure to various sources of HIV infectivity, including semen. Newly infected cells were detected in the cervical submucosa 3-4 days after exposure to a primary HIV isolate. At earlier times, extensive and stable binding occurred when cervical surfaces were exposed to virions or seminal cells. Cervical mucus provided some protection for the endocervical surface, by physically trapping virio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

12
116
0
12

Year Published

2007
2007
2022
2022

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 115 publications
(140 citation statements)
references
References 37 publications
(49 reference statements)
12
116
0
12
Order By: Relevance
“…13 Previous studies have also identified a role for CVF in the trapping of HIV virions, thus, preventing infection. 14,15 Recent studies have detected a correlation between several immuneresponse molecules in CVF and the incidence of subclinical premature rupture of membranes (PROM), which leads to preterm birth. 16,17 During pregnancy, CVF could contain amniotic fluid (AF) derived from the uterus, due to either the disruption or parallel secretions of the chorionic-decidual interface.…”
Section: Introductionmentioning
confidence: 99%
“…13 Previous studies have also identified a role for CVF in the trapping of HIV virions, thus, preventing infection. 14,15 Recent studies have detected a correlation between several immuneresponse molecules in CVF and the incidence of subclinical premature rupture of membranes (PROM), which leads to preterm birth. 16,17 During pregnancy, CVF could contain amniotic fluid (AF) derived from the uterus, due to either the disruption or parallel secretions of the chorionic-decidual interface.…”
Section: Introductionmentioning
confidence: 99%
“…Explants were placed with the mucosal side facing up in the top chamber of Millicell filter inserts (Millipore) (diameter, 12 mm; pore size, 0.4 m). The lateral edges of the explants were sealed with 3% agarose, as described previously (11,30,31). The orientation of the explants was monitored using a stereomicroscope (Stereomaster; Fisher Scientific).…”
Section: Methodsmentioning
confidence: 99%
“…[63], in den regionalen Lymphknoten innerhalb von etwa 5 bis 6 Tagen und im ganzen Körper verteilt, einschließlich des Nervensystems, innerhalb von etwa 10 bis 14 Tagen, wobei ein Unterschied in der Geschwindigkeit der Verbreitung besteht, wenn primär Zellen der Tonsillen oder der rektalen Mukosa infiziert wurden [64].…”
Section: Hiv-2unclassified